Membangun Batasan Keagamaan: Analisis Wacana Kritis Terhadap Meme Hadis Tashabbuh Sebagai Narasi Larangan Ulang Tahun - Ekatul Hilwatis Sakinah; Syahidil Mubarik Mh (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2025)
The practice of celebrating birthdays has become a site of contestation in religious discourse, where the hadith tashabbuh is used as the key argument for prohibition. This debate has not only occurred in traditional spheres but has also spread to the digital realm. This study aims to analyze the discourse on birthday prohibition based on the hadith tashabbuh meme on Instagram through the lens of Norman Fairclough's Critical Discourse Analysis (CDA) model. The findings of this study reveal two crucial points. First, the birthday prohibition meme exposes the mechanism of simplifying the meaning of the hadith by disconnecting (decontextualizing) the hadith tashabbuh from its original military/situational context. At the textual level, the hadith is reduced to an imperative slogan supported by linguistic strategies that tend to judge or blame, and reinforced by algorithmic strategies that trigger polarization (high engagement) at the level of discourse practice. Second, at the level of social practice, the ideological construction in this discourse actively reaffirms the Salafi Puritan ideology that focuses on purifying Islamic teachings. This discourse functions as a practice of religious identity boundary-work that creates a dichotomy between true Muslims and negligent Muslims. Thus, the hadith tashabbuh has been transformed into a digital tool of power that gives high normative power to narrow interpretations, forcing the audience to negotiate their religious identity in the digital space.